Pengolahan Limbah Kopi Saring Menjadi Briket di Desa Lamkeunung Kecamatan Darussalam Kabupaten Aceh Besar - Firdus, Firdus -; Gani, Asri -; Mursal, Mursal (Universitas Negeri Padang, 2025)
The need for renewable energy is increasingly pressing as fossil fuel reserves dwindle. Waste filtered coffee grounds, produced in large quantities by thousands of coffee shops in Banda Aceh and Aceh Besar, have significant potential for processing into environmentally friendly briquettes. Community service activities in Lamkeunung Village, Darussalam District, Aceh Besar Regency, were conducted to optimize this potential through technical training, provision of modern equipment, institutional strengthening, and marketing strategies. The results of the activities demonstrated increased community capacity, the formation of business institutions, and improvements in the quality and quantity of briquette production. In addition to its economic impact, this activity also contributed to the reduction of organic waste. Laboratory tests showed that briquettes made from filtered coffee waste had a calorific value of 5349.4 Cal/g, a moisture content of 2.5%, an ash content of 18.3%, a density of 0.82 g/cm³, and a compressive strength of 1.179 kgf/mm².